Camellia rostrata, a new species of yellow camellias from Southwest China - Liu, Zhen-Wen; Chai, Sheng-Feng; Wu, Fang-Yuan; Ye, Pin-Ming; Jiang, Chang-Jie; Zhang, Zhi-Rong; Yu, Xiang-Qin; Ma, Jin-Lin; Yang, Shi-Xiong (Phytotaxa, 2020)
Camellia rostrata S.X.Yang & S.F.Chai is described and illustrated as a new species from Guangxi, China. It is morphologically closest to C. debaoensis R.C.Hu & Y.Q.Liufu, but can be easily distinguished by its abaxially glabrous leaf surface, 1.0−1.5(−2.0) cm long pedicel, powdery puberulent inner surface of bracteoles, sepals, and petals, sparsely pubescent inner filaments base, and triangle globose or ellipsoid capsule with pointed beak. The conservation status of this new species was assessed as Critically Endangered (CR).